PENGARUH FLY ASH DAN LEGIN TERHADAP PERKEMBANGAN BIJI DAN PRODUKSI KACANG HIJAU (Vigna radiata L) - Maizar; Nursamsul Kustiawan (UIR Press, 2021)
The purpose of the research was to know the effect of Fly Ash and legin interaction on seed development and green bean production (Vigna radiata L), and the main influence of each treatment. The study used Completely Randomized Design (RAL) that consisted of two factors: Fly Ash waste with 4 treatment levels, i.e without fly ash, giving flay ash 1.0; 1.5 and 2.0 kg plots, and Legin Inoculation with 4 treatment levels, i.e without legin, inoculation of legin 5.0; 10.0 and 15.0 g / kg of seed. The results showed that the interaction of legin and fly ash inoculation did not affect the growth of green bean seeds, such as changes in seed moisture content, changes in dry seed weight, the rate of dry matter seed collecting (KPBK), effective seeding time (WPE), number of pods and weight of 100 grains seed. However, it affected the percentage of pods and the weight of dry seed harvest. Inoculation of 10 g of legin and 1.5 kg of fly ash was sufficient to produce the highest yield. Legin inoculation affected all parametrs observed. Inokulasi green beans with 10.0 g legin/kg seeds show the best seed development and production for all parameters that were observed. Fly ash feed affected all observation parameters. Giving 1.5 kg of fly ash/plot was sufficient for green bean plants to produce high seed development and production.